La investigación diacrónica sobre el español de Canarias: una visión historiográfica - Medina López, Javier (2023)
This article presents the development of research on the history of the Spanish language in the Canary Islands from a dialectal and historiographical perspective. We have considered both the contributions that conceive the current state of Canarian speech as an uninterrupted historical process, as well as those that rely on a methodology based on the transcription of historical documents. The latter are mainly part of the “Project for the Historical Study of Spanish in America”, carried out by the Asociación de Lingüística y Filología de América Latina (ALFAL) since 1993. In both cases, the bibliographical relationship will serve as the status quaestionis in this field of Canarian research. Today we have an extensive bibliographic panorama that shows how Canarian Spanish has evolved historically in the context of the Castilian expansion towards the Atlantic since the beginning of the 15th century.